Impact of Novel Dissimilar Shape Ternary Composition-Based Hybrid Nanofluids on the Thermal Performance Analysis of Radiator - Sahoo R.R.; Kumar V. (My University, 2025)
The thermal performance analysis of a radiator with a dissimilar shape nanoparticles, i.e., cylindrical (CNT)-platelet (graphene), spherical (Al2O3)-platelet (graphene), and spherical (Al2O3)-cylindrical (CNT) composition-based hybrid nanofluid for a coolant flowrate of 6 l/min, air velocity of 10.6 m/s, and 1.3% vol. faction of nanofluid has been studied and compared. Results revealed that a hybrid nanofluid as a coolant enhances the exergy-energy performance of the radiator. In this study, the cylindrical (CNT)-platelet (graphene) hybrid nanofluid results a decrement in the performance while the spherical (Al2O3)-platelet (graphene) hybrid nanofluid yields a better performance with coolant flowrate and air velocity. Particle shape has influenced a significant effect on the second law efficiency, exergy change, and irreversibility, which increases with an increase in air velocity, and volume fraction of hybrid nanofluid. However, the spherical (Al2O3)-platelet (graphene) hybrid nanofluid has 3.5%, 3.6%, and 1.12% higher performance index, exergy change in coolant, and second law efficiency, respectively, compared to the cylindrical (CNT)-platelet(graphene)-based hybrid nanofluid. Furthermore, results divulge that the nanoparticle shape has a notable impact on the performance of an automobile radiator. The spherical (Al2O3)-platelet (graphene) hybrid nanofluid exhibits supercilious over other shapes considered, and hence, it is more effective to use as a radiator coolant for enhancing the thermal performance. © 2021 American Society of Mechanical Engineers (ASME). All rights reserved.